The Role of Packaging in Consumer Buying Behavior: A Case of Selected Small-Scale Entrepreneurs in Arusha City - Lomayani, James (British Journal of Marketing Studies, 2021)
This study sought to examine the role of packaging among the small-scale entrepreneurs in consumer buying behavior in Arusha City. The study used a quantitative approach to collecting and analyzing data from a total of 219 respondents. Closed-ended questionnaires were used to collect data. The findings revealed that the label of the package is important in the decision buying process, the quality of the packaging material is important during the buying process and packaging color impacts consumer behavior during the buying process. Society culture, business culture, customer’s family culture, and customer’s lifestyle culture were important factors towards customers buying behavior. Finally, the study revealed that the existence of the relationship between the small-scale entrepreneurs packaging practices and the buying behavior of consumers in Arusha City was a factor for small-scale entrepreneurs in the study area to compete with other products from outside the country. The study recommended that small-scale entrepreneurs in Arusha City should be creative and innovative in terms of packaging. It was also recommended that the Government through the Small Industries Development Organization (SIDO) should train the small-scale entrepreneurs in Arusha City on packaging related matters to promote customer buying behavior.